Molecular and in vivo Functions of the CDK8 and CDK19 Kinase Modules - Dannappel, Marius Volker; Sooraj, Dhanya; Loh, Jia Jian; Firestein, Ron (Frontiers in Cell and Developmental Biology, 2019)
CDK8 and its paralog, CDK19, collectively termed ‘Mediator Kinase’, are cyclin-dependent kinases that have been implicated as key rheostats in cellular homeostasis and developmental programming. CDK8 and CDK19 are incorporated, in a mutually exclusive manner, as part of a 4-protein complex called the Mediator kinase module. This module reversibly associates with the Mediator, a 26 subunit protein complex that regulates RNA Polymerase II mediated gene expression. As part of this complex, the Mediator kinases have been implicated in diverse process such as developmental signalling, metabolic homeostasis and in innate immunity. In recent years, dysregulation of Mediator kinase module proteins, including CDK8/19, has been implicated in the development of different human diseases, and in particular cancer. This has led to intense efforts to understand how CDK8/19 regulate diverse biological outputs and develop Mediator kinase inhibitors that can be exploited therapeutically. Herein, we review both context and function of the Mediator kinases at a molecular, cellular and animal level. In so doing, we illuminate emerging concepts underpinning Mediator kinase biology and highlight certain aspects that remain unsolved.